Pemilihan Siswa Terbaik Melalui Metode Pendukung Keputusan WP (Weighted Product) - Wina Yusnaeni (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - Decision support system is a system which could help in determining the selection in a variety of fields. In determining the decision by one or more of the criteria referred to by multikriteria is sometimes considered to be complicated because of the uncertainties include factors that influence will be information and data are also used. SMAN 14 bekasi is a regional secondary school in bekasi, the electoral system is still the best student of the subjective. Therefore, the necessary decision support methods that will help the processing of the data in terms of the criteria is not only based on the value of multikritaria only. Weighted Product method is one method that is used as a decision support system to help resolve for nurturing with a decision support system with multikriteria. The use of the WP method is done with the next lighter weight value improvement of calculation value preferences of each alternative with the final result of the calculation of the value of the preference relation. From those results in doing perangkingan so can the highest value on students with grades i.e. 5 0043 and ranked second with a grade 7 student 0038. Keywords: Decison Support System, Weighted Product method, preference relation